Severe Malnutrition With Cachexia On Geriatric: A Case Report - Nuri Nurhasanah Sugandi; Angelika Augustine; Diva Tiara Mega; Florensia Windri Samara; Grasberg Dandhi Sifa Sikoway; Paskalina Sylvi Aprilia Huik; Satrio Sukarno Atmosudirjo; Sefrina Tania; Sharifa Novembriana; Steven Zerin Putra Kusmawan (Medical Clinical Update, 2023)
Malnutrition refers to deficiencies, excesses or imbalances in a person’s intake of energy and/ornutrients1. Geriatric malnutrition is often associated with functional impairment, increased infectionand morbidity and mortality rates2. According to the World Health Organisation (WHO), theglobal prevalence of malnutrition in the elderly is 1.3% - 47.8%. The prevalence of malnutrition was found to be high in hospitals, in Indonesia it is estimated to range from 33-70%3. Malnutrition is often associated with cachexia. Cachexia occurs due to imbalance between basal metabolic rate(BMR) that persistent increase and inadequat calorie or protein intake, which is known as malnutrition. Factors that cause cachexia include digestive factors4.